Deleuze and politics - Buchanan, Ian, 1969-; Thoburn, Nicholas, 1970- (Deleuze connections., 2008)
This volume in the Deleuze Connections series debates and extends Deleuze's political thought through engagement with contemporary political events and concepts. Against recent critique of Deleuze as a non-political thinker, this book explores the specific innovations and interventions that Deleuze's profoundly political concepts bring to political thought and practice. The contributors use Deleuze's dynamic theoretical apparatus to engage with contemporary political problems, themes and possibilities, including micropolitics, cynicism, war, democracy, ethnicity, friendship, revolution, power, fascism, militancy, and fabulation. Approaching Deleuze's politics from the disciplines of political theory, philosophy, literature, cultural studies, and sociology, the book is designed to appeal to a diverse audience. The essays in this volume focus on three key issues The ontology of Deleuze's political philosophy The philosophical debate between Deleuze and contemporary critical theory The application of Deleuze's political philosophy to real-world events